A new strategy for the reinforcement of paraffin-based fuels based on cellular structures: The armored grain — Ballistic characterization. (May 2023) - Bisin, Riccardo; Paravan, Christian
Abstract: Slow regression rate of the solid fuel is the main limitation for the use of hybrid rocket engines in high thrust applications. Paraffin-based fuels tackle this limitation thanks to the entrainment mass transfer. In this study, ballistic behaviors of conventional polymeric fuel (ABS) and paraffin-based blends are studied and compared with those of the armored grains . These latter are a new generation of fuels featuring 3D printed cellular structures embedded in the wax-based grain. The ballistic characterization focuses on the evaluation of the regression rate ( r f ) and its dependence on the oxidizer mass flux. Relative ballistic grading of the formulations is pursued via thickness over time methods and an optical technique for r f determination. The armored grains are reinforced by gyroid structures that are 3D printed using three different polymers (ABS, PLA, and Nylon 6) and two relative densities (10% and 15%). Despite the slow burning behavior of the printing polymers, the embedded reinforcement enhances the r f of the paraffin-based formulations, with percent increases ranging from +48% to +91%. This result could be explained by the uneven and irregular texture of the burning surface promoting turbulence (and therefore, propellant mixing) and convective heat transfer. For both the armored grains and the paraffin-based formulations, blending the pristine paraffin wax with polymeric additives results in more viscous formulations and in a r f reduction. Armored grain combustion performance makes this novel fuel an interesting candidate for high-thrust hybrid rockets. Highlights: Armored grains embed 3D-printed structures for paraffin-based fuel reinforcement. Gyroid is taken as suitable 3D-printed open-cell reinforcing structure. Armored grains enable fuel reinforcement with limited impact on melt layer viscosity. Armored grains show faster regression rates (+48% to +91%) than conventional blends. Embedded structure provides a combination of fast regression and strong mechanical properties.